4, 7-Diarylbenzo[c][1, 2, 5]thiadiazoles as fluorophores and visible light organophotocatalysts. Issue 20 (30th August 2022) - Taylor, Dominic; Malcomson, Thomas; Zhakeyev, Adilet; Cheng, Shengxian; Rosair, Georgina M.; Marques-Hueso, Jose; Xu, Zhengtao; Paterson, Martin J.; Dalgarno, Scott J.; Vilela, Filipe
Abstract : A library of 26 electron donor-acceptor organophotocatalysts based on the benzo[ c ][1, 2, 5]thiadiazole (BTZ ) group has been developed. These visible light organophotocatalysts were then used in a Minisci-type alkylation of heteroarenes under both batch and continuous flow conditions. Abstract : Electron donor–acceptor (D–A) systems based on the benzo[ c ][1, 2, 5]thiadiazole (BTZ ) motif have been extensively researched for use in photovoltaics or as fluorescent sensors. However, their use as potential visible-light organophotocatalysts has not received any in-depth study. Here we report the synthesis, characterisation, and application of a library of 26 D–A compounds based on the BTZ group. By varying the donor groups whilst keeping the BTZ acceptor group the same, we have been able to systematically modify the photocatalyst's optoelectronic and photophysical properties. These photocatalysts were then validated using a Minisci-type decarboxylative alkylation of electron deficient heteroarenes as a test reaction under both batch and continuous flow conditions.